Recent Advances in Trigeminal Neuralgia and Its Management: A Narrative Review - Burman, Sourav; Khandelwal, Ankur; Chaturvedi, Arvind (Journal of Neuroanaesthesiology and Critical Care, 2021)
Trigeminal neuralgia (TN) is a chronic facial pain condition that affects one or more divisions of the trigeminal nerve (5th cranial nerve). It can be idiopathic, primary, or secondary. The cornerstone of the therapy has been antiepileptic medications, peripheral nerve blocks with various neurolytic agents, and surgical procedures. With the advent of newer technologies, minimally invasive neurolytic techniques like low-level laser therapy and ozone injection have revolutionized the management of TN. Novel drugs like vixotrigine and eslicarbazepine have been promising in reducing the frequency and severity of attacks. Inhaled carbon dioxide too has shown promising results in initial trials. Neuromodulation has given robust data in controlling neuralgic pain especially refractory to medical management. Pulsed radiofrequency has been used with increasing success and the side effects like dysesthesia and paresthesia are less. Cryotherapy, neural prolotherapy, and fiber knife techniques have helped us believe that TN can be controlled and cured. The need of the hour is to develop and explore newer modalities for trigeminal neuralgia treatment with minimum side effects. In this narrative review, we have tried to shed light into the newer modalities of treatment of TN along with new clinical classification for better disease recognition and management.
Keywords: anticonvulsants; facial pain; neuromodulation; pulsed radiofrequency; trigeminal neuralgia